Sedition Laws: A Scrutiny with Reference to Freedom of Speech and Expression in Democratic India in View of Transformative Constitutionalism - Rajvardhan,; Muskan Ganwar, (AG Volumes, 2026)
This chapter explores the intricate balance between sedition laws and the constitutional guarantee of freedom of speech and expression in the context of democratic India, with a focus on transformative constitutionalism. Sedition laws, originally conceived to safeguard national security, have increasingly been scrutinized for their potential infringement upon fundamental rights, particularly the right to free speech. In light of the evolving landscape of constitutional jurisprudence and the transformative aspirations embedded in India's constitutional framework, this study critically examines the compatibility of sedition laws with the principles of democratic governance. The chapter delves into the historical development of sedition laws in India and their application over time, emphasizing instances where their implementation may have curtailed legitimate dissent and stifled the democratic spirit. Drawing from landmark judicial pronouncements, the analysis scrutinizes the constitutional validity of sedition laws, considering their alignment with the evolving understanding of freedom of speech and expression in the era of transformative constitutionalism. Transformative constitutionalism, as a guiding principle, underscores the need for constitutional interpretations that advance the transformative goals of justice, equality, and dignity. This chapter discusses how the judiciary's role in interpreting sedition laws is pivotal in aligning legal norms with the transformative constitutional ethos, ensuring that these laws do not become tools for suppressing dissent or stifling democratic discourse. Through an interdisciplinary approach, the chapter draws on legal precedents, scholarly perspectives, and constitutional philosophy to elucidate the evolving dynamics between sedition laws and freedom of speech in democratic India. By shedding light on the delicate balance between national security concerns and individual liberties, this chapter contributes to the ongoing discourse on the recalibration of sedition laws within the framework of transformative constitutionalism in a vibrant and evolving democracy.